PENGENALAN DASAR PENGGAMBARAN PADA PEMBELAJARAN JARAK JAUH - Agnatasya Listianti Mustaram (PROSIDING SERINA, 2021)
The 2021/2022 Semester period has come to an end. Many challenges in learning and teaching process for the lecturers and students have come throughout the way, from the beginning until almost the end of the semester. The learning methods adjustment at the university level seems to be very slow and full of twists and turns. The provisional assumption of the cause is because of there has not been any bridging program that helps adapting the method that is given in high school level with the one that is experienced in university level. When the offline method is applied in the university, the problem is easier to overcome with the orientation and introduction program for the new students. But in this pandemic learning situation where everything goes online, the orientation and introduction program for the new students went not as optimal as the offline. The virtual attendance at the campus and the meeting in an unreal meeting-room are not the best solution that can fulfill the needs of getting to know the new learning environment for the new students comprehensively. Ideally, the introduction of the new environment and education system in university level needs to be done since the students are still at the high school. Especially for architecture student, another adaptation that needs to be done is the learning process that involves visual language as the main tools on the daily basis. For that reason, the explanation about online learning that includes drawing process that will be experienced by the prospective architecture students in the beginning of the studies become really important. The writing method of this article is based on the community service activity on 100 High schools (PKM 100 SMA) that is organized by Universitas Tarumanagara for the High school students that is going to continue their studies to e higher level, through online meetings. On this occasion, the students of SMA Katolik Rajawali Makassar are given some knowledge about learning process that will be experienced in the beginning of Architecture studies with some overview about the difference about offline and online learning. In conclusion, introduction program about drawing in architecture studies for the high school students helps the SMA Katolik Rajawali Makassar students to have a better understanding about studying architecture at the university level.